Evolutionary Traits In Digital Spam: History ,Types, Techniques and Anti Spam Solutions - B. Mukunthan, M.Arunkrishna (International Journal of Advanced Science and Technology, 2020)
The emerging technology has led to the development of various platforms through which millions of people collaborate and communicate with each other. Spamming is the action of sending unsolicited messages through electronic messaging system. Spam is a form of platform manipulation. Spam message can be sent over multiple communication medium such as email,Instant Messages(IM), Online Social Networks(OSN) etc. Statistics show that a large proportion of internet traffic are spam. The person who spreads unsolicited contents to others are known as spammers. Spammers intentionally send messages to recipients who did not grant permission to send them. most of the messages are based on advertisements in which some of them are source of security breaches and lead to phishing or malware attack .This is because the spammers present their contents as valuable or as real one, and send them to the user. The authentic users mistake the spam information as an important one.